Stereotip Terhadap Perempuan Melalui Karakter Jeng Yah Dalam Series Gadis Kretek - Noni Octavia; Ningsi Demanto; Septia Intan Nurzannah (Dinasti Review, 2024)
Films and other cultural media not only present stories, but also messages and values conveyed through characters, plots, and themes including about gender stereotypes. The topic still exists, women are portrayed as passive figures, focusing only on domestic roles, while men are depicted as having more dominant roles. It triggers injustice and discrimination against women. Gender disparities are rooted in gender stereotypes towards men and women. The research focuses on the stereotypical portrayal of women through the character Jeng Yah in five episodes of the Cretaceous Girls series on Netflix. By using qualitative methods with critical discourse analysis of Sara Mills to analyze gender representation in the series in question. Some of the main points that indicate gender stereotypes against women are: women can only do certain jobs deemed appropriate to them, women do not have full control over their own lives, including important decisions that affect their freedom/future, women are often regarded as bearing